Pretomanid for tuberculosis: a systematic review. (January 2022) - Gils, Tinne; Lynen, Lutgarde; de Jong, Bouke C.; Van Deun, Armand; Decroo, Tom
Abstract: Background: Outcomes of treatment of tuberculosis patients with regimens including pretomanid have not yet been systematically reviewed. Objectives: To appraise existing evidence on efficacy and safety of pretomanid in tuberculosis. Data Sources: Pubmed, clinicaltrials.gov. and Cochrane library. Study eligibility criteria: Quantitative studies presenting original data on clinical efficacy or safety of pretomanid. Participants: Patients with tuberculosis. Interventions: Treatment with pretomanid or pretomanid-containing regimens in minimum one study group. Methods: Two authors independently extracted data and assessed risk of bias. Data on efficacy (early bactericidal activity, bactericidal activity, end-of-treatment outcomes and acquired resistance) and safety were summarized in tables. Mean differences in efficacy outcomes between regimens across studies were calculated. Results: Eight studies were included; four randomized controlled trials on 2-week early bactericidal activity in rifampicin-susceptible tuberculosis, three trials with randomized rifampicin-susceptible tuberculosis arms and a single rifampicin-resistant tuberculosis arm (two on 8-week bactericidal activity, one on end-of-treatment outcomes), one single-arm trial with end-of-treatment outcomes in highly resistant tuberculosis. Activity of pretomanid–moxifloxacin–pyrazinamide was superior to standard treatment on daily change in colony-forming units at days 0–2, 0–56 and 7–56 and time to culture conversion in rifampicin-susceptible tuberculosis (hazard ratio: 1.7; 95% CI 1.1–2.7), but not at end of treatment in one study. This study was stopped due to serious hepatotoxic adverse events, including three deaths, in 4% (95% CI 2–8) patients on pretomanid–moxifloxacin–pyrazinamide and none in controls. In patients with uncomplicated rifampicin-resistant tuberculosis on pretomanid-moxifloxacin-pyrazinamide treatment, 91% (95% CI 59–100) had favourable end-of-treatment outcomes. In patients with highly resistant tuberculosis, 90% (95% CI 83–95) on pretomanid–bedaquiline–linezolid had favourable outcomes six months after treatment, but linezolid-related toxicity was frequent. No acquired resistance to pretomanid was reported. Conclusions: Evidence suggests an important role for pretomanid in rifampicin-resistant and highly resistant tuberculosis. Trials comparing pretomanid to existing core and companion drugs are needed to further define that role.